Study on ocular anomalies in pediatric patients with special reference to congenital anomalies - Paul, Leena; Kuli, Jawahar Jyoti (International Journal of Research in Medical Sciences, 2021)
Background: Aim of the study was to study the proportion, clinical and etiological profile of congenital ocular anomalies in pediatric patients and limit its magnitude wherever possible so that preventable blindness can be dealt effectively. Methods: Present study was carried out in AMCH, Dibrugarh during the period of July 2018-June 2019. Total 1850 pediatric cases were examined, VA testing was done by Snellen’s chart or clinical judgment by HM, PL and PR also with Allen pictures in preschool children and in infants’ pupillary response and OKN were done. Examination under general anesthesia was done when necessary for posterior segment evaluation and IOP estimation. Results: Proportion congenital ocular anomalies were found to be 13.72%. Male:female ratio was found to be 1.8:1 where majority of cases were within 4 years of age. Most common congenital anomaly was congenital cataract followed by uveal coloboma, microphthalmos and anophthalmos etc. Majority of congenital cataract were in first birth rank and in 4.33% cases parents gave history of consanguinity. Conclusions: The prevalence of congenital anomaly varies in different aspects like age, sex, dwelling, socioeconomic class etc., factors like maternal infection, medication during pregnancy and maternal nutrition may have influence on production of congenital anomalies. Treatable congenital anomaly like congenital cataract, congenital glaucoma, eyelid coloboma etc. should be managed by ophthalmologist. Various demographic and mainly maternal factors which are found in study give a clue for further study on those group of people to get a conclusion for the etiology of ocular congenital anomalies concerned.